Facilitators of and Barriers to Effective Preceptorships for Pre-licensure Nursing Students: What Nursing Faculty Need to Know - Suja P. Davis PhD, RN, CGRN (SAGE Publishing, 2024)
Introduction Preceptorships offer prelicensure nursing students the opportunity to meet their clinical objectives by working one-on-one with a registered nurse (RN). Although preceptorships can be provided for any clinical course, most prelicensure nursing programs offer them during the final semester. Preceptorships provide a bridge between academic study and the real world of nursing. By acting as a teacher, role model, evaluator, and person who can help a student to socialize with the profession, a preceptor can reduce the reality shock experienced by new nurses and provide them with realistic expectations about the nursing profession. The recent nursing shortage has inadvertently led to a preceptor shortage and forced the nursing leadership to become dependent on available RNs, including those without preceptor training or experience. Purpose This practice update paper aimed to address the facilitators and barriers associated with preceptorships for prelicensure nursing students and discuss the proposed solutions for effective clinical preceptorship based on evidence and the author's personal reflections. Conclusion The major facilitators were the discussion of nursing program expectations, the selection of teaching strategies with real-world examples, the creation of a structured weekly plan to promote learning, and the consideration of alternative teaching approaches. The major barriers were preceptors' dual responsibilities to students and patients, challenging students, and the lack of experienced preceptors. The proposed solutions included obtaining support from the nursing leadership team to ensure that the preceptor had a balanced workload, developing the emotional competence of the preceptor, addressing challenging students through a three-way conference with the student, the preceptor, and the clinical faculty and a written plan to ensure student progress, having the nursing leadership conduct periodic assessments of the preceptor pool, and ensuring that appropriate training was offered to candidates who were willing to become preceptors.